Preparation and Diels–Alder reactions of 1′-heterosubsituted vinylimidazoles. Issue 23 (3rd June 2015) - Ray, Abhisek; Mukherjee, Sabuj; Das, Jayanta; Bhandari, Manoj K.; Du, Hongwang; Yousufuddin, Muhammed; Lovely, Carl J.
Graphical abstract: Abstract: A Diels–Alder/rearrangement sequence has been pursued in our lab en route to a number of oroidin dimers. In order to access the fully substituted core of these molecules, 1′, 2′-disubstituted 4-vinylimidazoles were required as dienes. The preparation of a series of 4-vinylimidazoles containing substituents on the vinyl moiety via hydroalumination/electrophilic trapping or hydrosilylation is described. These derivatives undergo Diels–Alder reactions with N -phenylmaleimide to provide the tetrahydrobenzimidazole derivatives. The cycloadducts derived from halosubstituted systems can undergo elimination, leading to the corresponding dihydrobenzimidazole, whereas the silyl and stannyl derivatives provide the corresponding 4-substituted tetrahydrobenzimidazole.